A multi-centre observational study of HIV, tuberculosis and risk of chronic lung disease in urban West Africa. (15th November 2022) - Fink, Douglas L.; Oladele, David A.; Slack, Abigail J.; Odubela, Oluwatosin; Musari-Martins, Tomilola; Okechukwu, Adaobi; Adetayo, Kemi; Opaneye, Sola; Abubakar, Rufai; David, Agatha; Cai, James; Quaderi, Shumonta; et al.
Abstract : Objective: HIV and tuberculosis (TB) are risk factors for non-communicable chronic lung disease (CLD). Despite the high prevalence of these infections in West Africa, there are no studies that compare CLD between people with HIV and HIV-negative populations in this setting. This study sought to quantify the contribution of HIV and TB infection in addition to conventional CLD risk factors, such as tobacco and biofuel exposure, to CLD in urban West Africa. Design: A multi-centre cross-sectional study was conducted in three community clinics in Lagos, Nigeria between 2018 and 2019. Methods: Spirometry, questionnaires and clinical records were used to estimate prevalence of CLD and association with risk factors. Results: In total, 148 HIV-negative individuals and 170 HIV-positive individuals completed the study. Current cigarette (11 of 318, 3.5%) and lifetime domestic biofuel (6 of 318, 1.8%) exposures were low. Airway obstruction (33 of 170, 19.4% vs. 12 of 148, 8.1%, P  = 0.004) and CLD (73 of 170, 42.9% vs. 34 of 148, 23%, P  < 0.0001) were more prevalent in people with HIV compared with the HIV-negative group. HIV infection [odds ratio 2.35 (1.33, 4.17), P  = 0.003] and history of TB [odds ratio 2.09 (1.04, 4.20), P  = 0.038] were independently associated with increased risk of CLD. Conclusion: HIV and TB far outweigh conventional risk factors, including tobacco and domestic biofuel exposure, as drivers of non-communicable CLD in urban West Africa. Current global policy for CLD may have limited impact on CLD in this setting. Enhanced prevention, diagnosis and management strategies for incident HIV and TB infections are likely to have a significant impact on long-term lung health in sub-Saharan Africa.